PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN LAPORAN TAHUNAN (Students' Journal of Accounting and Banking, 2014)
This research was conducted to determine whether the mechanisms of good corporate governance can effect the level of disclosure information in the annual reports on manufacturing companies listed in Indonesia Stock Exchange.The population used in the research is a manufacturing company listed on the Indonesia Stock Exchange with the 2009-2011 research period. For research purposes in the selection of the sample using purposive sampling method to obtain 153 sample companies that fit the criteria. Processing and data analysis in thisresearch using multiple linear regression.The results of research indicate that Corporate Governance mechanisms affect the level of disclosure in the annual report. While partially just managerial ownership,concentration ownership, auditcommittees and company size significantly influence the level of disclosure in the annual report. Other independent variables such as institutional ownership, the proportion of independent directors has no effect on the level of disclosure in the annual report.Keywords: Disclosure, Corporate Governance Mechanisms, Manufacturing, Annual Reports